2022
DOI: 10.1093/eurheartj/ehac220
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy in the era of advanced cardiovascular imaging

Abstract: Historically, autopsy contributed to our current knowledge of cardiovascular anatomy, physiology, and pathology. Major advances in the understanding of cardiovascular diseases, including atherosclerosis and coronary artery disease, congenital heart diseases, and cardiomyopathies, were possible through autopsy investigations and clinicopathological correlations. In this review, the importance of performing clinical autopsies in people dying from cardiovascular disease, even in the era of advanced cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Over recent decades, however, there has been a decrease in autopsy rates in many countries across the globe ( Figure 3 ). 47 , 91 , 94 In general, increasing age and comorbidity burden are associated with lower rates of post-mortem examination, including both medicolegal external examination and autopsy. 15 , 22 , 47 , 95 , 96 This is problematic as it is well known that several comorbidities such as diabetes mellitus, kidney disease, and epilepsy are associated with higher risk of SD.…”
Section: Resultsmentioning
confidence: 99%
“…Over recent decades, however, there has been a decrease in autopsy rates in many countries across the globe ( Figure 3 ). 47 , 91 , 94 In general, increasing age and comorbidity burden are associated with lower rates of post-mortem examination, including both medicolegal external examination and autopsy. 15 , 22 , 47 , 95 , 96 This is problematic as it is well known that several comorbidities such as diabetes mellitus, kidney disease, and epilepsy are associated with higher risk of SD.…”
Section: Resultsmentioning
confidence: 99%
“…In the era of transcatheter aortic valve implantation (TAVI), a multi-center autopsy series of patients dying after the procedure showed that in the acute postimplantation time frame, the procedure could be associated with aortic annular rupture and thromboembolic ischemic stroke. In particular, bulky calcification in the left ventricular outflow tract under the left-coronary aortic cusp could be a risk factor for rupture during TAVI (46). Autopsies have also helped to demonstrate that the depth of prosthesis implantation is one of the most important predictors of the need for pacemaker implantation due to conduction disorders soon after transcatheter selfexpandable aortic valve implantation (47).…”
Section: Challenges Arising From Modern Visualization Advancesmentioning
confidence: 99%
“…Autopsies are valuable for elucidating the pathophysiologic mechanisms of novel and poorly understood diseases by enabling deep phenotyping of tissues throughout the body [ 5 ]. Autopsies played a critical role in understanding the pathologic changes in patients dying from acute COVID-19.…”
Section: Introductionmentioning
confidence: 99%